A Review on E-Learning During Covid-19 Pandemic Situation - Sofia Moran-Suarez (Tecno Scientifica Publisher, 2022)
As a result of the novel coronavirus (COVID-19) outbreak in Mexico, there has been a pressing need to rethink how pupils receive their education. Students were required to keep a social distance from their peers and families, but they also had to adapt to online study. To avoid the spread of the dangerous disease, remote learning has become the standard. Educators around the world were obliged to transition to online instruction, particularly at the university level, due to the unexpected spread. There are some pupils that are open to the idea of online education. It's true that some people have reservations about the transition from traditional to online learning. There appear to be a number of ways in which educators might contribute to improving the quality and efficiency of virtual education. The following are summaries of a number of publications discussing ways to improve online teaching and learning. In the vast majority of studies, it has been shown that adapting to remote learning was a wise decision. However, a study found that some students dislike online learning because of personal and technological concerns. The stress and worry that students experience as a result of distance learning is another concern. According to current studies, online learning may also have psychological effects in conjunction with a difficult learning process. It highlights significant academic articles, recognizes ideas, and points to areas in need of additional research.